SISTEM INFORMASI ARSIP ELEKRONIK (E-ARSIP) BERBASIS WEBSITE DI KANTOR KECAMATAN BLANAKAN - Tiara Iffatunadia (2023)
The benefits of applying technology have been felt in various fields, including the field of document archiving. Some of the benefits that can be felt with the application of technology in document archiving, namely, the process of searching for documents feels easier, faster, more precise, and more. The Blanakan District Office has duties and responsibilities that must be carried out properly and in practice they carry out administrative processes, where the process requires document archiving. However, the increase in the volume of documents which continues to grow every day, causes the document filing and management process at the Blanakan sub-district office to experience several obstacles, including the length of the document retrieval process, damage to documents, less organized document arrangement, and incomplete documents. because it's scattered. The solution that the author offers to the Blanakan sub-district office to deal with these obstacles is to create a website-based electronic archive information system (E-Archive). The system design method in this E-archive information system research will use the waterfall method. Using Laravel as the framework, using PHP and HTML as the programming language as well as MySQL as the database. User requirements will be described using UML (Unified Modeling language) and system testing will be carried out using the black box testing method. This research resulted in an E-Archive information system for the Blanakan District Office that was able to pass all trial scenarios well. It is hoped that this E-Archive information system will be able to handle all the problems that occur in the document filing process at the Blanakan District Office.